Ensuring safety and feasibility for resection of pediatric benign ovarian tumors by single-port robot-assisted laparoscopic surgery using the da Vinci Xi system - Xu, Deqiang; Gao, Heyun; Yu, Shanzhen; Huang, Guangbin; Lu, Dan; Yang, Kun; Zhang, Wei; Zhang, Wen (Frontiers in Surgery, 2022)
Background Single-port robot-assisted laparoscopic surgery (S-RALS) is rarely applied in pediatric surgery. There is still no study on the application of S-RALS for resection of pediatric benign ovarian tumors. The current study aimed to investigate the safety and feasibility of S-RALS for resection of pediatric benign ovarian tumors using the da Vinci Xi system. Methods The clinical data of three patients who underwent S-RALS for resection of benign ovarian tumors in the Department of Pediatric Surgery, Zhongnan Hospital of Wuhan University from May 2020 to September 2021 were retrospectively analyzed. The mean age of these children was 7.9 years (5.8–9.3 years). One was a case of bilateral ovarian tumors, and the other two were cases of right ovarian tumors. Results All three patients successfully underwent the resection of ovarian tumors through S-RALS without conversion to laparotomy. The average operation time was 180 min (118–231 min). The average amount of blood loss was 20 ml (10–35 ml). No drainage tube was placed. All postoperative pathological types of ovarian tumors were mature cystic teratomas in the three cases. All patients started a liquid diet 2 h after surgery. The average length of postoperative hospital stay was 4.7 days (3–7 days). No tumor recurred, no surgical site hernia occurred, and the wound healed very well with a cosmetic scar in the lower umbilical crease during the postoperative follow-up for 6–18 months. Conclusion S-RALS has the advantages of less surgical trauma, quick postoperative recovery, and a cosmetic scar in the lower umbilical crease. It is safe, effective, and feasible for pediatric benign ovarian tumors.